A combined Bi-LSTM-GPT Model for Arabic Sentiment Analysis - Karfi , Ikram El; Fkihi , Sanaa El (International Journal of Intelligent Systems and Applications in Engineering, 2023)
This research investigates the efficacy of ensemble learning within the field of Arabic sentiment analysis. Ensemble learning, which combines predictions from multiple models to enhance accuracy, has shown promising results when compared to individual models. Hence, we propose an ensemble learning model that integrates two robust models: a Bidirectional Long Short-Term Memory (BiLSTM) model and a Generative pre-trained transformers (GPT) model. The GPT model has previously demonstrated effectiveness in various Arabic natural language processing (ANLP) tasks. To examine the performance of our ensemble model, we separately trained the BiLSTM and transformer-based model using three different datasets. We combined the models by aggregating their final probabilities for each class. Through multiple experiments, we compared the effectiveness of the proposed ensemble model with the standalone models. The results clearly indicate that the ensemble learning models outperform the standalone models in Arabic sentiment analysis. Specifically, the proposed ensemble model that demonstrated an accuracy increase of nearly 7% when compared to the best standalone model.